2009
DOI: 10.1098/rspb.2008.1661
|View full text |Cite
|
Sign up to set email alerts
|

Manipulating grooming by decreasing ectoparasite load causes unpredicted changes in antagonism

Abstract: It is thought that allogrooming is practised strategically in order to establish, maintain and reinforce social bonds between group members, exchanging one altruistic behaviour for a different form of reciprocated benefit at a later date. Correlational evidence supports this, but evidence of causality is lacking. We reduced parasite loads in eight meerkat Suricata suricatta groups, generating a substantial decrease in grooming. Contrary to the predictions, overall antagonism did not increase. However, within g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 32 publications
0
20
0
1
Order By: Relevance
“…Several experimental studies of rodents and viverrids have demonstrated that when ectoparasites are experimentally removed, grooming rates decrease within social groups; these experiments provide several pieces of evidence to support the ideas that the presence of ectoparasites stimulates grooming behavior and that grooming functions to reduce ectoparasite load (Hawlena et al 2008; Madden and Clutton-Brock 2009; Hillegass et al 2010). Further, experimental studies in several vertebrate species in which individuals were prevented from grooming themselves showed that grooming reduces ectoparasite loads (Eckstein and Hart 2000; Mooring et al 1996).…”
Section: Discussionmentioning
confidence: 79%
“…Several experimental studies of rodents and viverrids have demonstrated that when ectoparasites are experimentally removed, grooming rates decrease within social groups; these experiments provide several pieces of evidence to support the ideas that the presence of ectoparasites stimulates grooming behavior and that grooming functions to reduce ectoparasite load (Hawlena et al 2008; Madden and Clutton-Brock 2009; Hillegass et al 2010). Further, experimental studies in several vertebrate species in which individuals were prevented from grooming themselves showed that grooming reduces ectoparasite loads (Eckstein and Hart 2000; Mooring et al 1996).…”
Section: Discussionmentioning
confidence: 79%
“…Based on the differences in infection sites among the parasites included here and their low metabolic demands within second intermediate hosts, cross-reactive immunity is perhaps the most probable mechanism, consistent with a growing emphasis on the role of host immunity in determining coinfection outcomes (31,(33)(34)(35)(36). That host diversity generally had stronger inhibitory effects on parasite loads than did parasite diversity may stem from the greater potential for low-competence hosts to function as population sinks for invading parasites, whereas immune-mediated competition associated with coinfection acts primarily to weaken persistence of parasites that have already colonized (2,37).…”
Section: Discussionmentioning
confidence: 92%
“…[36]), irrespective of whether the exchange involves a time delay or not. For instance, allogrooming may be demanded as a service by aggressively challenging another group member, as suggested by positive correlations between aggression given and grooming received for example in meerkats, Suricata suricatta [246] and Barbary macaques, Macaca sylvanus [129]. Aggression and threats of eviction from the group may help dominants to obtain a large variety of cooperative behaviours from subordinate group members ('pay-to-stay'; [77][78][79]194,247]).…”
Section: Trading and The Reciprocal Exchange Of Commoditiesmentioning
confidence: 99%